Optimizing Whatsapp Features in Improving English Speaking Proficiency: A Classroom Action Research - Sesa, Haris; Margana, Margana (JOLLT Journal of Languages and Language Teaching, 2025)
The problem underlying this study is the low level of English proficiency among students, while the importance of technology in education is increasingly recognized. To overcome this, the study implements a Classroom Action Research (CAR) approach by using WhatsApp features such as voice messages and video calls as media to encourage students to practice speaking. The purpose of this action is to provide opportunities for students to develop their speaking proficiency. This research was conducted through three cycles of action involving the planning, implementation, observation, and reflection stages. Data were collected through pre-tests, observations during cycles one, two, and three, and interviews with students. Data analysis focused on measuring the increase in speaking fluency, reduction in pronunciation errors, decrease in the frequency of pauses, and increase in students’ confidence levels, as part of the reflection process in each cycle. The results of the action cycles showed a significant increase in students’ speaking fluency. In the first cycle, many students reached 81-90 words per minute, while in the second cycle, the speaking rate increased to 91-100 words per minute. Some students even reached 100-110 words per minute in the third cycle. The frequency of pronunciation errors decreased consistently, and no students showed an increase in the number of errors after the actions in each cycle. The decrease in the frequency of pauses during speaking also indicated an increase in students’ fluency and confidence. Overall, the reflections from these CAR cycles indicate that the use of the WhatsApp features is contributes in increasing speaking fluency, reducing pronunciation errors, decreasing the frequency of pauses, and increasing students’ confidence in speaking English. However, further action cycles are needed to continue to support students who are still at a low level of fluency and help more students achieve the expected standard.